Unmet needs in psychiatry and emerging novel pharmacological agents - ARICIOĞLU, FEYZA (KURE ILETISIM GRUBU A S, 2013)
Despite huge amount of efforts and resources spent to improve the pharmacotherapeutic tools to treat major psychiatric disorders such as depression and schizophrenia, there still exist unmet needs in the field. Treatment resistance, non-adherence, and severe adverse effects such as diabetes mellitus type II, extrapyramidal side effects, etc. are among the unmet needs commonly faced by clinicians, probably due to the fact that the pathophysiology of both schizopherenia and depression have not been fully elucidated. Today, neither the monoamine hypothesis of depression nor the dopamine hypothesis of schizophrenia explains either disorder in full. In spite of its widespread presence throughout the brain, the glutamatergic system has remained almost unexplored with respect to drug discovery for psychiatric illnesses. Recently, the promising outcomes of intravenous use of ketamine to overcome resistance to antidepressant treatment and the administration of a nitroprusside infusion to address resistance to antipsychotics in the treatment of schizophrenia have drawn attention to the glutamatergic system.
Keywords: depression; schizophrenia; drug therapy; treatment-resistant; ketamine; nitroprusside; GLUTAMATE RELEASE; TARGETS; PLASTICITY; MODULATORS; RECEPTORS; RILUZOLE; TRIAL